P51 Advancing Quality (AQ) Reducing Variation and Improving Quality and Outcomes for patients with Chronic Obstructive Pulmonary Disease (COPD) in the North West of England. (12th November 2015) - Roberts, J; Szwandt, D; Hammond, S
Abstract : Introduction and objectives: COPD patients in the North West of England die 15 years earlier than expected. Advancing Quality is a programme of work where a common approach supports quality improvement that focuses on clinical pathways. Methods: A regional clinical expert group agreed the AQ COPD evidence based measures (clinical interventions) in February 2013. The AQ COPD clinical interventions are: Within 4 Hours Hospital Arrival: Oxygen - Bronchodilator - Corticosteroid - Antibiotic Therapy. During Hospital Admission: Smoking Cessation - Pulmonary Rehab - Inhaler Technique - Written Self-Management Plan - Spirometry – Home Oxygen - Appropriate End of Life Care – follow up. Following an initial pilot, AQ COPD went live in September 2014. AQ is a proven approach to improve quality, providing standardisation and transparency for providers and commissioners. Results: Trusts aim to deliver all the interventions that the patient is eligible for, this is known as the Appropriate Care score (ACS). More patients are receiving "perfect care" with AQ, (see Figure 1 ). Trusts participating in AQ had a mean LOS of 4.7 days compared to 5.7 days for non-participating trusts and average bed days for patients re-admitted in participating trust was 5.5 days compared to 11.8 days in non- participating trusts. Trusts participating saw their readmission rate fall to 20.1% over the period (a reduction of 9%). Conclusion: A regional standardised approach, focused on a small but significant set of clinical interventions, can have a significant impact on improving patient care and outcomes. In 2015/16 North West CCGs have commissioned AQ COPD across 15 of the 21 Acute Trusts. An AQ incentive framework was also developed for providers and commissioners that supports "doing the right thing" collaborative events ensure that ongoing sharing of best practise happens and we have future plans to expand into Primary and Community Care.